Hack attack. - Gill, John (Times Higher Education, 2008)
The article reports on the development of the Flaws online security system to prevent automated hacking by School of Computing Science lecturer Jeff Yan of Newcastle University in England and doctorate student Ahmad Salah El Ahmad in 2008. They were able to determine the vulnerability of the Captcha system used to protect global electronic mail (email) services and websites from hacking attacks. Yan notes the significance of the discovery of the vulnerability to internet users.